The escape - Baldacci, David (Baldacci, David. John Puller novel., 2014)
"When John Puller's older brother Robert inexplicably escapes from the military's most secure prison, where he's being held for national security crimes, Puller finds himself part of an investigation to hunt down his own brother. As he digs more deeply into the case, Puller discovers troubling details about his brother's conviction and that someone is out there who doesn't want the truth to ever come out." --